Information System Design Hotel Reservation Booking at Wisma XYZ - Setiawan; Bagus Mulya Ramdani (ASIAN PUBLISHER, 2022)
Wisma XYZ is engaged in the public service business providing lodging, meeting rooms, sports facilities and other major events (seminars, graduations, exhibitions, weddings etc.) The stages of research carried out are collecting data through literature studies, interviews, and observations, as well as analyzing software requirements, building databases with MySQL, designing interfaces using CSS, javascript, HTML, and PHP, testing programs as the final stage in making web-based application. Based on the results of the user acceptance test, this Reservation Order information system is able to facilitate interested parties (in this case students, lecturers, academics and study program staff) to obtain the required information, become a solution in efforts to improve academic services and simplify the management process because it is easy accessed through web media